Analisis Rasio Keuangan untuk Menilai Kinerja Keuangan Pada Pt Summarecon Agung Tbk - Yuniarti Pratyka; Wiryawan Suputra Gumi (STIMI Handayani Denpasar, 2023)
This study discusses the Analysis of Liquidity, Solvency, and Profitability Ratios to assess the Financial Performance of PT. Summarecon Agung Tbk. The purpose of this research is to know and analyze the financial performance at PT. Summarecon Agung Tbk. using the liquidity, solvency and profitability ratio method for the 2018-2022 period. The data analysis technique used is descriptive quantitative through measurement of financial performance measured by 3 ratio analysis, namely: 1) Liquidity ratios (Current Ratio and Quick Ratio), 2) Solvability ratios (Debt to Asset Ratio and Debt to Equity Ratio), and 3 ) Profitability Ratios (Return On Assets and Return On Equity). Based on the results of the study it can be concluded that the assessment of the financial performance of PT. Summarecon Agung Tbk. In terms of the liquidity ratio in terms of the Current Ratio from 2018-2022 is quite good and in terms of the Quick Ratio from 2018- 2022 the company's condition is not good. Assessment of financial performance in terms of solvency ratios in terms of the Debt to Asset Ratio and Debt to Equity Ratio from 2018- 2022 The company's condition is not good because it is above the company's industry standards. And the assessment of financial performance in terms of profitability ratios in terms of Return On Assets and Return On Equity from 2018-2022 is very poor.